Perbandingan Kualitas Poros Roda Depan Honda Beat Orisinil dan Imitasi - Aini Lostari; R. Yudi Hartono (Universitas Muhammadiyah Ponorogo, 2018)
Industrial industrial products on the market are manipulating between original and imitation products, products that are imitated are sold at lower prices and have lower quality. However, the product is in great demand by the public. The research aims to determine the quality level of the original and imitation front axle, both from the hardness, and the chemical composition of the material, and to compare the prices given with quality. This research was conducted by testing the chemical composition using a spectrometer and brinell hardness testing carried out in the STTQ Bungah Gresik mechanical engineering laboratory. In addition, the research uses materials with two front wheel shafts for testing chemical composition with six wheel shaft specimens both original and imitation. Research with spectrometer testing showed that the shaft is included in the low carbon steel group with an original carbon content of 0.192% and an imitation shaft of 0.155%, also included in the low alloy steel group because the number of alloys is less than 2.5%, while in hardness testing brinell found the original shaft harder than the imitation shaft, either on the surface or inside with a percentage of 52.14% difference between the two. For the comparison between price and quality given between the two shafts, the percentage where the value of the comparison of violence is greater is around 49.97% to 52.14% rather than the price ratio of around 20% given by the producer, it would be better for consumers to buy original shafts than the imitation.